Internal control system analysis of fraud prevention at pt bank sulselbar - FADLI YASIN (International Journal of Multidisciplinary Research and Studies, 2023)
The essence of this investigation aimed to dissect the inner workings of PT Bank SULSELBAR's system to thwart deceit. This inquiry took place across 5 branches of the aforementioned bank, spanning a moon's cycle from July of 2023. Employing a quantitative research approach, the selection of participants was no happenstance; rather, it was a calculated choice achieved through purposive sampling, yielding a respondent pool of 76 individuals. Armed with firsthand data, the method of data collection involved the dispersal of self-administered questionnaires. The evaluation of hypotheses hinged upon the grand edifice of the Structural Equation Model (SEM), specifically assessed via Smart-PLS 3.0. Ultimately, the findings echoed in unison: the internal control construct wields a constructive sway over the bulwark against fraud.